Regulation of Hippocampal cGMP Levels as a Candidate to Treat Cognitive Deficits in Huntington’s Disease - Saavedra, Ana (Public Library of Science, 2013)
Huntington’s disease (HD) patients and mouse models show learning and memory impairment associated with hippocampal dysfunction. The neuronal nitric oxide synthase/3',5'-cyclic guanosine monophosphate (nNOS/cGMP) pathway is implicated in synaptic plasticity, and in learning and memory processes. Here, we examined the nNOS/cGMP pathway in the hippocampus of HD mice to determine whether it can be a good therapeutic target for cognitive improvement in HD. We analyzed hippocampal nNOS and phosphodiesterase (PDE) 5 and 9 levels in R6/1 mice, and cGMP levels in the hippocampus of R6/1, R6/2 and Hdh(Q7/Q111) mice, and of HD patients. We also investigated whether sildenafil, a PDE5 inhibitor, could improve cognitive deficits in R6/1 mice. We found that hippocampal cGMP levels were 3-fold lower in 12-week-old R6/1 mice, when they show deficits in object recognition memory and in passive avoidance learning. Consistent with hippocampal cGMP levels, nNOS levels were down-regulated, while there were no changes in the levels of PDE5 and PDE9 in R6/1 mice. A single intraperitoneal injection of sildenafil (3 mg/Kg) immediately after training increased cGMP levels, and improved memory in R6/1 mice, as assessed by using the novel object recognition and the passive avoidance test. Importantly, cGMP levels were also reduced in R6/2 mouse and human HD hippocampus. Therefore, the regulation of hippocampal cGMP levels can be a suitable treatment for cognitive impairment in HD.